PERENCANAAN BIAYA DAN WAKTU UNTUK PEKERJAAN STRUKTUR PROYEK PEMBANGUNAN GEDUNG - Pramono, Didiek; Furuhitho, X; Sulardi, Sulardi; Arifiyanti, Nabilla (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Planning is one of the vital functions in project management activities. One of the plans is to make a Budget Plan (RAB). In the writing process, the author uses 2 methods, namely RAB which refers to the PUPR Ministerial Regulation No. 1 of 2022 and RAB which refers to field conditions (contractors). The author conducts an basically the RAB contractor is made as economical as possible. If it is too low, it will pose a risk to the contractor. If it is too high, the contractor is less likely to win the tender. The author conducts a planning analysis because in reality the contractor's RAB with PUPR no. 1 Year 2022 will be different in cost and time because it is influenced by factors such as wages, material prices, equipment prices, worker coefficients and components in AHSP. This analysis was conducted with the aim of knowing the comparison of the contractor's RAB with PUPR No. 1 Year 2022. Based on the case study conducted on the Rectorate Building Project of the Indonesian International Islamic University (UIII), the author will calculate the cost and time of the Ministerial Regulation No. 1 Year 2022 with contractors. This research was conducted only to review the structure of the rectorate building. Planning is done by calculating the volume, AHSP, RAB, weight and duration of work. The cost of the contractor structure work is Rp. 52,081,676,945.61 with a duration of 346 days. The results of the planning with the guidelines for the PUPR regulation No. 1 of 2022 obtained a cost of Rp. 53,022,244,952.58 with a duration of 275 days and the difference in costs is Rp. 940,568,006.96 and a duration of 7 days.